2009
DOI: 10.1128/aem.02709-08
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Diversity, and Potential Mobility of Extrachromosomal Elements Related to the Bacillus anthracis pXO1 and pXO2 Virulence Plasmids

Abstract: The presence of a pXO1-and/or pXO2-like plasmid(s) in clinical isolates of Bacillus cereus sensu stricto and in strains of the biopesticide Bacillus thuringiensis has been reported recently, and the pXO2-like plasmid pBT9727 and another pXO2-like plasmid, pAW63, were found to be conjugative. In this study, a total of 1,000 B. cereus group isolates were analyzed for the presence of pXO1-and pXO2-like replicons and for the presence of pXO2-related conjugative modules. pXO1-and pXO2-like replicons were present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 45 publications
1
52
0
Order By: Relevance
“…plasmids that are closely related to Bacillus anthracis pX02. Plasmids of this group include pX02, pAW63, and pBT9727, and a recent survey also identified pX02-like plasmids encoding VirB11 homologs in Bacillus isolates from a variety of environmental niches (137). Many of these plasmids encode functional T4SS, as shown by their capacity to transfer small mobilizable plasmids (137).…”
Section: Gram-positive T4ssmentioning
confidence: 99%
“…plasmids that are closely related to Bacillus anthracis pX02. Plasmids of this group include pX02, pAW63, and pBT9727, and a recent survey also identified pX02-like plasmids encoding VirB11 homologs in Bacillus isolates from a variety of environmental niches (137). Many of these plasmids encode functional T4SS, as shown by their capacity to transfer small mobilizable plasmids (137).…”
Section: Gram-positive T4ssmentioning
confidence: 99%
“…Indeed, Hu et al have demonstrated that ϳ7% of B. cereus/B. thuringiensis species can have a pXO1-like plasmid and ϳ1.5% a pXO2-like plasmid (15). This was particularly underlined for some virulent B. cereus strains (i.e.…”
mentioning
confidence: 99%
“…For strain VD045, potential plasmid transfer through conjugation has been reported, and the identification at the species level has been questioned (45). Thus, at least VD045 may actually represent a B. cereus strain which is able to take up the plasmid carrying the genes responsible for insect toxicity.…”
Section: Discussionmentioning
confidence: 99%